Performance Analysis and Operation and Maintenance Cost Requirements for Rapak Di Drainage - Yusnita, Maya; Wulandari, Esti; Nugroho, Laksono Djoko (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Inadequate drainage infrastructure often leads to waterlogging during rainfall, emphasizing the need for urgent repairs. This study assesses the performance condition of the Rapak Dalam Drainage system using a quantitative and qualitative approach, including field observations, direct measurements, and hydrological data analysis. The findings indicate that the drainage system is rated at a "Good" performance level, with a functional capability of 80.56%. Although the system effectively manages water in most areas, certain components require immediate repairs to maintain optimal functionality. To enhance drainage performance, this study recommends routine inspections, timely maintenance, and sediment management to prevent blockages. Additionally, upgrading drainage infrastructure, optimizing water flow through improved design, and implementing community-based maintenance programs are suggested to ensure long-term efficiency. These measures will help mitigate flooding risks and improve urban water management in Samarinda.